Ageneiosus uranophthalmus, a new species of auchenipterid catfish (Osteichthyes: Siluriformes) from river channels of the central Amazon basin, Brazil - Ribeiro, Frank Raynner Vasconcelos; Py-daniel, Lúcia Rapp (Neotropical Ichthyology, 2010)
Ageneiosus uranophthalmus is described from river channels of the central Amazon basin, Brazil. The new species is widely distributed in the Amazon and is distinguished from its congeners by the V-shape snout and eye laterally placed and dorsally oriented, more visible in dorsal view than in ventral view. Ageneiosus uranophthalmus shows a range of variation on color pattern when compared with its congeners. This and other differences are described and discussed herein. © 2010 Sociedade Brasileira de Ictiologia.
Keywords: Ageneiosus; Auchenipteridae; Osteichthyes; Pisces; Siluriformes